Fruit bat migration matches green wave in seasonal landscapes. (10th June 2022) - Hurme, Edward; Fahr, Jakob; ,; Eric‐Moise, Bakwo Fils; Hash, C. Tom; O'Mara, M. Teague; Richter, Heidi; Tanshi, Iroro; Webala, Paul W.; Weber, Natalie; Wikelski, Martin; Dechmann, Dina K. N.
Abstract: Migrating grazers and carnivores respond to seasonal changes in the environment and often match peaks in resource abundance. However, it is unclear whether and how frugivorous animals use phenological events to time migration, especially in the tropics. The straw‐coloured fruit bat Eidolon helvum, Africa's most gregarious fruit bat, forms large seasonal colonies throughout much of sub‐Saharan Africa. We hypothesized that aggregations of E. helvum match the timing of their migration with phenologies of plant growth or precipitation. Using monthly colony counts from across much of the species' range, we matched peak colony size to landscape phenologies and explored the variation among colonies matching the overall closest phenological event. Peak colony size was closest to the peak instantaneous rate of green‐up, and sites with closer temporal matching were associated with higher maximum greenness, short growing season and larger peak colony size. Eidolon helvum seem to time their migrations to move into highly seasonal landscapes to exploit short‐lived explosions of food and may benefit from collective sensing to time migrations. The link between rapid changes in colony size and phenological match may also imply potential collective sensing of the environment. Overall decreasing bat numbers along with various threats might cause this property of large colonies to be lost. Remote sensing data, although, indirectly linked to fruiting events, can potentially be used to globally describe and predict the migration of frugivorous species in a changing world. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.